The Influence of Interpersonal Communication and Motivation on Employee Performance at PT Lotte Shopping Avenue Indonesia - Suryanto Suryanto; Ahmad Cik; Kumba Digdowiseiso (Equivalent: Jurnal Ilmiah Sosial Teknik, 2024)
The purpose of this study is to analyze how the influence of interpersonal communication and motivation on employee performance partially, This research was conducted at PT. Lotte Shopping Avenue Indonesia. Data processing using the validity and reliability test and regression and correlation test using SPSS 19. The results showed in the partial test the influence of competence and career coaching on employee performance. Between Interpersonal Communication (X1) and Motivation (X2) on Employee Performance (Y) shows a positive relationship. This shows the two independent variables, Interpersonal Communication (X1) and Motivation (X2) have affected Employee Performance (Y). Through hypothesis testing it is possible to know that interpersonal communication and motivation to prove each have positive and significant effect on employee performance equal to 77.0%. This means that 77.% The dependent variable of employee performance can be explained by the independent variable that is interpersonal communication and motivation. It shows that there are still other factors equal to 23.0% to employee performance. The magnitude of this influence shows that interpersonal communication and motivation is an important element in improving the performance of employees of PT. Lotte Shopping Avenue Indonesia.